Journal of Preventive Medicine and Hygiene 2022
DOI: 10.15167/2421-4248/jpmh2021.62.4.1788
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gestational diabetes and its association with stillbirth, preterm birth, macrosomia, abortion and cesarean delivery among pregnant women: a national prevalence study of 11 provinces in Iran

Mitra Darbandi,
Shahab Rezaeian,
Mostafa Dianatinasab
et al.

Abstract: Summary Background Gestational diabetes mellitus (GDM) is one of the most common metabolic disorders during pregnancy that significantly affects perinatal outcomes. Objective The aim of this study was to determine the prevalence of GDM and its relation with the incidence of stillbirth, preterm birth, macrosomia, abortion and cesarean section (C-section) delivery in pregnant women. Methods This cross-sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Pregnant women developing gestational diabetes had a higher probability of delivering by caesarean section [20], which may further increase the probability of diabetes mellitus type 2 and hypertension disease in mothers at the next stages of their life [21]. Preterm delivery, macrosomia, abortion, pulmonary distress, stillbirth, and neonatal deaths have been considered among the most common outcomes of gestational diabetes [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women developing gestational diabetes had a higher probability of delivering by caesarean section [20], which may further increase the probability of diabetes mellitus type 2 and hypertension disease in mothers at the next stages of their life [21]. Preterm delivery, macrosomia, abortion, pulmonary distress, stillbirth, and neonatal deaths have been considered among the most common outcomes of gestational diabetes [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…There are also certain studies supporting evidence that caesarean section might be a risk factor of preterm birth, but other studies did not confirm this finding [18,19], reinforcing the need for further investigation. Women developing gestational diabetes also have a greater likelihood of pre-eclampsia and delivering by caesarean section [20], which further leads postnatally to increasing rates of type 2 diabetes and hypertension-related disorders [21]. Several evidence has also shown that mothers who deliver by caesarean section may be less probable to breastfeed, and/or more probable to delay breastfeeding initiation which may lead to increased rates of maternal and childhood adverse outcomes [22].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women developing gestational diabetes had a higher likelihood of delivering by caesarean section [ 20 ], which may further increase the probability of diabetes mellitus type 2 and hypertension disease in mothers at the next stages of their life [ 21 ]. Preterm birth, high newborn body weight, abortion, pulmonary distress, stillbirth, and neonatal deaths have been considered among the most common adverse outcomes of gestational diabetes [ 20 , 21 ]. However, in our study, we found no association between caesarean section prevalence and gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…There are also certain studies supporting that an increased caesarean sections’ rate might be a risk factor of preterm birth, but other studies did not confirm this finding [ 18 , 19 ], reinforcing the need for further investigation. Women developing gestational diabetes also have a greater likelihood of gestational hypertension and pre-eclampsia and delivering by caesarean section [ 20 ], which further leads postnatally to increasing rates of type 2 diabetes and hypertension-related disorders [ 21 ]. Much evidence has also shown that mothers who deliver by caesarean section do not frequently begin breastfeeding, or they postpone breastfeeding initiation, which could exert superior beneficial effects in both the mothers’ and their infants’ health [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…GDM is emerging as an important public health concern due to its association with severe perinatal outcomes, such as perinatal death and congenital malformations [ 6 8 ]. Maternal diabetes-induced congenital malformations can affect any developing organ or system.…”
Section: Introductionmentioning
confidence: 99%